Some effects of soil-moisture availability on above-ground production and reproductive allocation in Larrea tridentata (DC) Cov - Gary L. Cunningham; J. P. Syvertsen; J. F. Reynolds; Willson, J. M. (Oecologia, 1979)
Data from the US/IBP Desert Biome validation studies indicate that above-ground production and biomass allocated to reproduction in Larrea tridentata vary from one year to another depending upon the timing and extent soil-moisture availability. In an attempt to verify these observations and determine to what extent water availability can affect total above-ground production and reproductive allocation in this widely distributed warm desert shrub, a series of soil-moisture augmentation experiments were conducted. High levels of soil moisture had a greater effect on reproductive allocation than on total above-ground production. Enhanced soil moisture during the period of active growth increased total above-ground production and reduced the percentage of biomass allocated to reproduction. Enhanced soil moisture during the normal periods of little or no growth did not increase total above-ground production.
Keywords: article; articles; journal; journals; Larrea, reproduction; Larrea, soil moisture; Larrea,productivity; plant,Larrea tridentata